Comparison FEM study of microwave and radio frequency ablation in breast phantom model - Sanpanich, A.; Drechsel, H.; Angkhananuwat, W.; Khongkhanon, C.; Rattanakajornsak, R.; Phasukkit, P. (My University, 2012)
Thermal ablation by using energy from an electromagnetic wave in microwave and radiofrequency range is widely accepted as an alternative therapeutic maneuver for an internal cancer treatment as a breast tumor. However a comparison study between these two techniques are still an interesting topic especially in term of main control parameters, output and outcome of an expect coagulation zone. In this research, we propose a comparison investigation of microwave and radiofrequency ablation in a breast phantom model by using FEM. Our breast model is originally and specially designed as a multi-layer tissue in order to close to a real human breast organ. The simulation results show an interesting different output from these two EMW frequencies as an ablation power, treatment time and also coagulation area significantly. ©2012 IEEE.
Keywords: Breat cancer treatment; FEM; Microwave-radiofrequency comparison; Thermal ablation